Youth on the move in Somalia: Perspectives, vulnerabilities, and horizons - Villa, Victor; Belli, Anna (2024)
Within the Horn of Africa, effects of intensifying droughts and water scarcity, compounded by extreme poverty, political instability, and economic vulnerability, are driving large-scale displacements and frictions over dwindling resources. Somalia, which has reached 3.8 million displaced people in 2023, is recognized as a hotspot country that urges humanitarian assistance and development interventions to prevent further displacement and provide solutions for the youth and the generations to come. This study uses the International Organization of Migration's (IOM) Flow Monitoring Surveys (FMSs) to investigate the interplay of generational perspectives and the climate-conflict nexus in shaping human mobility patterns across different flow monitoring points in Somalia. Regression-based modelling is employed to examine how climate variability and conflict in the origin areas, along with gender, education and socio-economic background, affect migration intentions among different generations. Notably, the analysis highlights generational variations in migration decisions and experiences, shedding light on the distinct perspectives, vulnerabilities, and horizons of different age cohorts. These findings contribute to a nuanced understanding of generational differences in the context of climate change, conflict, and environmental challenges, and provide insights for designing policies and interventions that address the specific needs and aspirations of the youth on the move in Somalia.